A new species of Greenisca and two new species of Ovaticoccus from Italy (Hemiptera Coccoidea Eriococcidae), with a key to European genera of Eriococcidae. - Pellizzari, Giuseppina; Kozár, Ferenc (Zootaxa, 2011)
Three new eriococcid species from Italy are described and illustrated, namely Greenisca oreophila sp. n. off Poaceae, and Ovaticoccus exoticus sp. n. and O. agavacearum sp. n., off Agavaceae. Their morphological relationships are discussed and keys to Greenisca and Ovaticoccus species are provided, together with a key to the Eriococcidae genera so far known in Europe. A check-list of Italian Eriococcids is added.